The FUN MAPS: A youth sport scientific breakthrough - Visek, A. J.; Manning, H. M. (Olympic & Paralympic Coach, 2014)
Fun. Everyone wants to have it. However, few can easily describe what "it" is. Such is no longer the case - at least for kids participating in organized athletics. The FUN MAPS are the result of new and exciting sport science research that engaged hundreds of youth sport players, parents, and coaches in the creation of innovative, three-dimensional maps that identify the exact determinants of what makes sports fun for kids. Like any road map or sophisticated GPS system, the FUN MAPS display the entire landscape of fun and provide navigational directions for optimizing fun based on precise metrics. Much of the popular media buzz and excitement generated by this new research stems from the need and desire voiced by many to put the fun back into the ever increasing ultra-competitive youth sport environment. What`s more, the FUN MAPS are challenging one of the most common perceptions in the youth sport arena today - that "having fun" is synonymous with "goofing off". Not so, according to the FUN MAPS. Contrary to what many may think, fun does not come at the expense of individual athlete and team achievement efforts. In other words, it appears that greater athletic performance is more likely to be achieved if kids are engaged in the most fun sport experiences possible. So, exactly what is fun? The FUN MAPS are the scientific blueprints for an entire theory of fun known as the fun integration theory. To learn more and to see the FUN MAPS in their entirety, you can refer to the original scientific paper, "The fun integration theory: Towards sustaining child and adolescent sport participation" available via: • Human Kinetics in the Journal of Physical Activity & Health: http://doi.org/10.1123/jpah.2013-0180 • PubMed: http://www.ncbi.nlm.nih.gov/pubmed/24770788